Real-Time Implementation Of D-Q Control For Grid Connected Three Phase Voltage Source Converter - Mohamad Razali, Azziddin; Rahman, ,Mahmudur Azizur; A. Rahim , Nasrudin (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper investigates a new approach to develop and implement a virtual flux oriented control (VFOC) for the front-end three phase bidirectional voltage source converter (VSC) by adapting the principle operations of voltage oriented control (VOC) and power estimation used in virtual flux direct power control (VFDPC).The proposed VFOC operates with minimal number of sensors by avoiding the used of ac voltage supply sensors.In addition,the proposed control scheme utilizes the direct and quadrature (d-q) decoupling and feed-forward components to enhance the performance of front-end VSC during load and supply voltage disturbances.The steady-state as well as the dynamic performance of the proposed controller is presented and analyzed by means of the Matlab simulation, and verified through experiment.The ac-dc converter utilizing VFOC is able to produce adjustable dc output voltage,fixed switching frequency,unity power factor and low harmonic distortion of the line current.